Hearing people speak in different accents biases voice discrimination - Shane C. Santos; Aaliyah Kapadia; David R. Feinberg (Scientific Reports)
Abstract Voice discrimination is a fundamentally different task when matching utterances than when matching identity across different words. Discriminating between speakers of different languages makes the task even harder because unfamiliar languages contain different phonemes that are less easily matched. Discriminating between people with different accents may also be difficult as even if the same words are uttered, the phonemes are different. To test this, we created a set of voices using voice cloning that have the same or different identity or accent (UK, Poland, and China) and speaking different phrases. We tested how accent, sentences, and identify affected bias to conflate different identities as the same person. Contrasting identity between different and same increased bias to judge people as the same by about 62%. Contrasting accent between different and same independently increased bias to judge people as the same by about 10%. Contrasting between different and same sentences, changed bias to label people the same more when the accents were different than when they were the same. Our results are consistent with the idea that we are biased to think people typically speak with one accent. Thus, accents affect voice discrimination independently of language familiarity.